Listening to music and its reflection on the artistic output of the students of the Department of Art Education: سميعه فاضل كعود (Al-Academy, 2021)
The relationship between music and plastic arts can be viewed as an interdependent relationship, as they both develop imagination, focus and sensory perception, as well as the presence of some artistic concepts that music shares with the art of drawing, on this basis the rationale for this research aimed at identifying (the influence of music) was dealt with On the artistic output (drawing) of students of the Department of Art Education - College of Fine Arts) In the first chapter the problem of research, importance, terminology, boundaries and goal was addressed, and in the second chapter the researcher dealt with in the first topic the relationship between music and painting, and in the second topic the use of music in education. As for the third chapter in the research procedures, the researcher chose the descriptive approach to achieve the goal of the research, and she selected a sample of the fourth stage students in the Department of Art Education in the Faculty of Fine Arts at the University of Diyala. Drawing and students who do not use music, and after getting acquainted with that, the researcher prepared a form for analyzing the paintings. Two for the group that listens to music and two paintings for the group that does not listen to music while drawing chose four paintings. After analyzing these paintings for both groups, the researcher reached a number of results the most important ones are:1. The panels for students who listen to music show rhythm and harmony. As for students who did not listen to music, these elements did not appear.2. There is harmony, coordination and interaction in the use of color and its gradations in the work of students who listen to music, while this color interaction did not appear clearly in the work of students who do not listen to music.3. The distribution of shapes, blocks and lines appeared harmoniously in the work of students who listen to music while drawing, while the contradiction and rigid nature appeared in the work of students who did not listen to music. This research was concluded with recommendations and a list of sources. Key words: listening, music, mirroring.